2012
DOI: 10.3389/fpsyg.2012.00555
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Switching Attentional Focus during Finger Movements: An fMRI Study

Abstract: Research on motor-related attentional foci suggests that switching from an internal to an external focus of attention has advantageous effects on motor performance whereas switching from an external to an internal focus has disadvantageous effects. We used functional magnetic resonance imaging to investigate the neural correlates of switching the focus of attention. Two experimental groups were trained to apply one focus direction – internal or external – on a previously learned finger tapping sequence. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 74 publications
1
30
1
1
Order By: Relevance
“…Previous studies have implicated activities of motor-related areas in focus of attention (Kuhn et al, 2016;Zentgraf et al, 2009;Zimmermann et al, 2012), while our current findings indicate that the right frontoparietal network also has an important function in determining the attentional strategy most suitable for individuals during a motor learning task. The prefrontal cortex (including the frontal eye field) and the parietal cortex are strongly interconnected by fibers passing through the superior longitudinal fasciculus (Makris et al, 2005), and the frontoparietal network does contribute to attention control (Corbetta & Shulman, 2002;Dosenbach et al, 2008;Kehrer et al, 2015).…”
Section: Discussionsupporting
confidence: 48%
“…Previous studies have implicated activities of motor-related areas in focus of attention (Kuhn et al, 2016;Zentgraf et al, 2009;Zimmermann et al, 2012), while our current findings indicate that the right frontoparietal network also has an important function in determining the attentional strategy most suitable for individuals during a motor learning task. The prefrontal cortex (including the frontal eye field) and the parietal cortex are strongly interconnected by fibers passing through the superior longitudinal fasciculus (Makris et al, 2005), and the frontoparietal network does contribute to attention control (Corbetta & Shulman, 2002;Dosenbach et al, 2008;Kehrer et al, 2015).…”
Section: Discussionsupporting
confidence: 48%
“…Movement characteristics were maintained for a longer period even when all experimental groups later received an instruction to focus equally on speed and accuracy. Recent fMRI data on switching attentional focus direction for finger movements support this finding (Zimmermann et al, 2012).…”
mentioning
confidence: 67%
“…In another fMRI experiment, Zimmermann et al . () investigated the neural correlates of switching attentional foci. Results revealed that switching from a trained IF to an unfamiliar EF elicited a greater activation of the left lateral premotor cortex.…”
mentioning
confidence: 99%